THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY AND MANAGERIAL OWNERSHIP ON COMPANY VALUE WITH PROFITABILITY AS A MODERATING VARIABLE - Endah Supeni Purwaningsih (Journal of International Conference Proceedings (JICP), 2019)
This study aims to determine: (1) The effect of CSR on firm value, (2) The effect of managerial ownership on firm value, (3) The effect of CSR on firm value with profitability as a variable, (4) Effect of managerial ownership on firm value with profitability as moderating variable, (5) Effect of CSR and managerial ownership on firm value, (6) Effect of CSR and managerial ownership on the value of the company with profitability as a moderating variable. The sample of this study is the financial statements of mining companies in 2014 and 2015 using the purposive sampling method. There are a total of 46 companies that meet the criteria as research samples. The results of this study indicate that: (1) CSR has an effect on company value, (2) Managerial ownership does not affect company value, (3) Profitability as a moderating variable cannot moderate the effect of CSR on firm value, (4) Profitability as a moderating variable can moderate the influence of managerial ownership on firm value, (5) CSR and managerial ownership do not affect the value of the company, (6) Profitability as a moderating variable does not moderate CSR and managerial ownership of firm value.